Accurately Tunable AuNC‐ZIF Content Architecture Based on Coordination‐Dissociation Mechanism Enables Highly Brightness Dual‐Site Fluorescent Biosensor - Junyang Chen; Yuqian Wang; Runpu Shen; Wei Li; Sainan Gao; Zhikang Xiao; Qiyan Lv; Xiaojie Song; Jianzhong Xu; Gaoxiang Xu; Huifang Cui; Zhaohui Li (Advanced Science)
Abstract The quantum yield and fluorescence intensity of gold nanocluster (AuNC) nanocarriers are critical parameters for developing ultrasensitive biosensors. In this study, AuNCs‐zeolitic‐imidazolate‐framework (Au‐ZIF) nanocomposites are systematically constructed by impregnating AuNCs onto the ZIF‐8 surface through a coordination‐dissociation mechanism, resulting in a dual‐site fluorescence‐loaded structure. In this configuration, AuNCs are anchored to the external surface while the integrity of the inner cavity remains intact. The surface of ZIF‐8 induces a confinement effect on the configuration and electrons of AuNCs, significantly enhancing luminescence (18‐fold increase). The quantum yield of AuNCs exhibits an increase of more than 13‐fold, from 2.80% to 38.1%. This approach demonstrates broad applicability and maintains strong fluorescence across different ZIFs. Additionally, a novel nanocomposite, Au‐ZIF@carbon‐dots (CDs), is synthesized by encapsulating CDs into the inner cavity of Au‐ZIF. A ratiometric fluorescence detection platform is subsequently developed and incorporated into hydrogels for the quantitative detection of the pesticide triazophos. By employing an image‐processing algorithm, quantitative detection is achieved with a detection limit of 0.07 ng mL⁻1. The findings provide crucial insights into the relationship between the assembly and performance of AuNCs and ZIFs, offering guidance for designing ultrasensitive multifunctional biosensors applicable in the field of biosensing.